If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18=9+5(n+4)
We simplify the equation to the form, which is simple to understand
-18=9+5(n+4)
Reorder the terms in parentheses
-18=9+(+5n+20)
Remove unnecessary parentheses
-18=+9+5n+20
We move all terms containing n to the left and all other terms to the right.
-5n=+9+20+18
We simplify left and right side of the equation.
-5n=+47
We divide both sides of the equation by -05 to get n.
n=-9.4
| -2(j-3)= | | y-3=-1x-2 | | .5X-Y=30 | | 3x(x*3)=-5 | | 6x^3+2x^2-18x-6=0 | | 3(5x-6)+9=4(3x+12)+3 | | 4-(X)-8=28 | | b^2-6b+9= | | (4(r*R)-2r)=12 | | 8x-16=58 | | 4y+3=5x | | (4(r*R)-2r)=6 | | 4-(X)-8=4 | | c-9=47 | | 5x-1=-(2x+13) | | y-7=1x-5 | | 0.6g-0.333333333=-3.333333333 | | v^2=-10-7v | | 4-(X)-8=-20 | | 2+3=4+x | | -4x+70=230 | | 3(-Y-1)-3Y=3 | | (2r-1)=12 | | 4-(X)-8=-52 | | 6n+5n+3-2=7n+4n+18 | | 7x+3=2x-9 | | 10x-2y=-34 | | 4-Xx-8=-52 | | log(2x)=log(x+10) | | 4n-40=7(-2+7) | | 4+-7n=13-6n | | 5-.2x+.03x^2=0 |